2017
DOI: 10.1002/htj.21271
|View full text |Cite
|
Sign up to set email alerts
|

Performance of a single‐duct portable propane air conditioning system under different refrigerant charge levels

Abstract: The effects of the refrigerant charge on the performance of a portable propane air conditioning system have been evaluated and compared to nonportable systems in which the surrounding temperatures of the evaporator and condenser are not equal. This study aims to determine the similarities and differences in the performance of the two types of propane air conditioners under different charge levels, and to serve as a source of reference for future designs of portable air conditioners. The refrigerant charge was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…The cooling capacity of R290 is slightly lower than its R22 (Park et al, 2007). Siang and Sharifian, 2017 found that the cooling capacity of R290 increases gradually from -20% undercharged -+30% overcharged.…”
Section: Research Backgroundmentioning
confidence: 88%
“…The cooling capacity of R290 is slightly lower than its R22 (Park et al, 2007). Siang and Sharifian, 2017 found that the cooling capacity of R290 increases gradually from -20% undercharged -+30% overcharged.…”
Section: Research Backgroundmentioning
confidence: 88%
“…R290 is a natural refrigerant with a mass and volumetric cooling capacity of 87.7% and 54.2% higher than other refrigerants (R134a), respectively [6]. In other studies, R290 was used in air conditioning and heat pump systems [17,18]. It was found that there was an improvement of 16.71% in the COP value in the steam compression refrigeration cycle, and it was observed that the cooling capacity increased by approximately 35% [15,19].…”
Section: Introductionmentioning
confidence: 99%
“…In order to find out optimal charge quantity of different refrigerants, the performance of the heat pump and the suction pressure of compressor were experimentaly studied by Afshari et al [11]. At ambient temperature 20-35 • C, the variation of system parameters with different refrigerant charge was studied by Siang et al [12]. It was found that refrigeration capacity and performance coefficient can be improved by increasing refrigerant charge, while specific refrigeration capacity of the system decreased.…”
Section: Introductionmentioning
confidence: 99%